Agenesis of Third Molars in Orthodontic Patients attending Dhulikhel Hospital - Upadhyaya, Chandan; Adhikari, Bhoj Raj; Kafle, Dashrath; Humagain, Manoj (Orthodontic Journal of Nepal, 2012)
Aims and objective: The aim of this descriptive study was to determine the prevalence of agenesis or congenitally missing third molars in orthodontic patients attending Dhulikhel Hospital. Materials & Methods: A retrospective study of a total of 294 patients, of both genders ranging from 12 to 34 years of age who were orthodontically treated between August, 2010 to May 2012, were reviewed from the files of the Department of Orthodontics, Dhulikhel Hospital, Kathmandu University Hospital. The records included panoramic radiographs and study models of all patients with intra oral photographs at the beginning of treatment. Results: It shows that agenesis of one to four third molars was present in male group in 63 cases out of 94, i.e, 67.02% and in the female group in 85 cases out of 200, i.e. in 42.5%. In the group of male and female together, we found the agenesis of one to four third molars in 148 cases, which is 50.34 %. Conclusions: Data concerning the incidence of third molars agenesis belong to the essential characteristics of the dentition's status of the given population. Dental developmental anomalies can indicate the degree of genetic load of individuals and relatives. By analyzing the global term "agenesis of one to four third molars" it is possible to receive data, which are quite significant for the orthodontic treatment plan.